A multi-omics atlas of CAF subtypes reveals apCAF–M2 macrophage interactions driving immune resistance in glioma - Yubo Ren; Dengfeng Lu; Fei Wang; Zixuan Wang; Jinfeng Li; Run Huang; Yue Lu; Aojie Duan; Renjie Shou; Jiangang Liu; Zhouqing Chen; Zhong Wang; et al. (PLoS ONE, 2025)
Cancer-associated fibroblasts (CAFs) are a critical component of the glioma microenvi-ronment and play essential roles in tumor progression and resistance to immunotherapy. To comprehensively characterize CAF heterogeneity and their interactions with immune cells, we conducted an integrative multi-omics analysis incorporating single-cell and bulk RNA sequencing, spatial transcriptomics, and multiplex immunofluorescence. This approach identified nine distinct CAF subtypes with phenotypic and functional diversity, including tumor-like CAFs (tCAFs), myofibroblast-like CAFs (myCAFs), vascular CAFs (vCAFs), metabolic CAFs (meCAFs), proliferative CAFs (pCAFs), antigen-presenting CAFs (apCAFs), interferon-responsive CAFs (infCAFs), inflammatory CAFs (iCAFs), and a group of CAFs with unknown identity. Several subtypes were significantly associated with poor clinical outcomes. Notably, apCAFs engaged in extensive crosstalk with M2-polarized macrophages via TGF-β signaling pathways. Spatial transcriptomic pro-filing and immunofluorescence imaging revealed the co-localization of apCAFs and M2 macrophages at the tumor periphery, indicating the formation of an immunosuppressive niche. Moreover, AQP4 was identified as a specific marker of apCAFs, and its expression was significantly correlated with poor prognosis and resistance to immunotherapy. These findings offer a comprehensive atlas of CAF heterogeneity in glioma and highlight the therapeutic promise of targeting apCAF–M2 macrophage interactions or AQP4 to over-come immune resistance and improve clinical outcomes.